Inestabilidad institucional, evidencia para Colombia: la violencia y el crecimiento económico en el periodo 1950-2010. (2012)
The uncertainty in periods of institutional instability, reflected in violence, can destroy the endowments of physical and human capital in the economy and, discourage investment. The paper analyses the long-run impact of the violence on the Colombia’s economic growth, using annual time series data from 1950 to 2010. The negative relationship between violence, as measured by homicide rate, and economic growth is supported econometrically. The findings have a strong implication on educational and security policies in Colombia. The results suggest that it must make a concerted effort to improve institutional investment in education and safety in order to accelerate growth.